The Effect of Indirect Written Corrective Feedback to Arabic Language Intermediate Students’ in Kuwait - Hamed A. Alhumidi; Sani Yantandu Uba (European Scientific Journal, ESJ, 2016)
This study investigates the effect of indirect written corrective feedback to Arabic intermediate students in Kuwait. There are 20 participants altogether in this study, ten male and ten female. They each wrote two assignments on the same topic. No feedback was received on the first assignment, and the second was conducted after indirect feedback was offered to them on the first task. The results show that indirect feedback is effective in improving their writing and language skills. The results also indicated a higher number of spelling errors than any other errors. The findings of this study suggest some teaching implications which include raising students’ awareness of the need to avoid many writing errors. Teachers should not correct all students’ errors, but should only correct those errors which are deemed necessary to correct. Teachers should also focus their attention on teaching and learning tasks, which concentrate on indirect written feedback rather than direct feedback. Again, as the leaners seem to have more problems with spelling errors rather than any other errors, teachers should devise strategies which concentrate on improving such errors, and writing correct words. This study advocates a large scale of studies which cover the wider context of Kuwaiti intermediate students.